Regional Interpretation of Constantinopolitan Models in Byzantine 11th-Century Architecture - Zakharova, Anna V. (Actual Problems of Theory and History of Art, 2022)
The paper is dedicated to the process of adaptation of metropolitan trends in the architecture of Byzantine provinces in the 11th century. The author analyzes buildings in Macedonia, Attica, and Crete. These examples show how the main church type of this period was interpreted in different regions. The author discusses the particularities in the planning, style and technique, different versions of combining the metropolitan typology with older regional traditions, and modifications that depended on certain local conditions, models, or liturgical requirements. Thus, in the late 10th century a specific modification of inscribed cross church was created on Mount Athos, with two lateral apses that probably appeared in response to particular liturgical needs. It is likely that another addition to the Athonite type, the two-storey twin-domed narthex, also originated on Mount Athos as a replication of the venerated model (the Great Lavra katholikon) and/or in connection with housing the monastic libraries inside the churches. In the early 11th century other churches appeared reflecting these experiments with the basic Constantinopolitan type, representing its original and creative interpretations: the Church of the Holy Apostles in Athens and Panagia Chalkeon in Thessaloniki. Yet such examples remain unique. In Crete, in the first half of the 11th century, another version of the inscribed cross type emerges exemplified in the Churches of Zoodochos Pigi at Alikianou and St. Demetrius at Agios Demetrios near Rethymnon. These monuments have transitional character and combine the main features of the metropolitan type with older local peculiarities, such as the cross-shaped ground plan and niches in the eastern walls of the lateral cross-arms. The replication of these local traits was probably instigated by the donor, St. John Xenos, and relied on his earlier building, the katholikon of Myriokephala monastery (early 11th century). Later this local traits disappear and more standard versions of the inscribed cross churches spread in Crete.
Keywords: Byzantine architecture; inscribed cross church; athonite type; twin-domed narthex